The Joint Business Group (KUBE) and Urban Poverty Reduction at Wirobrajan, Yogyakarta City: What and How - Wifata, Erva (Jurnal Ilmiah Administrasi Publik, 2018)
This study frames two research questions. Firstly, what is the present status of the implementation of the KUBE program in Wirobrajan, Yogyakarta. Secondly, what are the constraining factors on implementing the KUBE program? Result shows that the implementation of Joint Business Group (KUBE) Program in Wirobrajan Sub-District, Yogyakarta Municipality has not been well implemented. There are six constraint factors to contribute to the failure of the KUBE implementation in reducing the urban povertion in Yogyakarta City. Likewise, Of the 31 groups formed, only 17 active groups remain while 14 other groups are inactive or dispersed. This study suggests that in the selection of business types, they should be in accordance with the skills and abilities of the KUBE member and adjust those needs with the surrounding community’s needs.